2022
DOI: 10.3390/catal12080916
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium Loading over Iron–Silica Interaction, Phase Evolution and Catalytic Behavior of Precipitated Iron-Based Catalysts for Fischer-Tropsch Synthesis

Abstract: Potassium (K) promoter and its loading contents were shown to have remarkable effects on the Fe–O–Si interaction of precipitated Fe/Cu/K/SiO2 catalysts for low-temperature Fischer-Tropsch synthesis (FTS). With the increase in K content from 2.3% (100 g Fe based) up to 7% in the calcined precursors, Fe–O–Si interaction was weakened, as reflected by ATR/FTIR, H2-TPR and XPS investigations. XRD results confirmed that the diffraction peak intensity from (510) facet of χ-Fe5C2 phase strengthened with increasing K l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…The results are shown in Supplementary Figures S4 and S5. The MnCuK-FeC catalyst shows signals of Fe 5 C 2 , MnO and CuO in the Raman spectra, while the CuZnAlZr catalyst shows signals of the four metal oxides (CuO, ZnO, Al 2 O 3 , ZrO 2 ), which corresponds to the XPS results in Supplementary Figure S3 (Zhuo et al, 2008;Ahmed et al, 2013;Liu et al, 2014a;Bauer, 2018;Mironova-Ulmane et al, 2018;Lee et al, 2021) Besides, the FT-IR results also show the chemical bonds contained in the two catalysts (Zheng et al, 2013;Jayarambabu, 2014;Elango et al, 2017;Naayi et al, 2018;Chang et al, 2022) The passivated MnCuK-FeC catalyst was pretreated by CO prior to the catalytic reactions, and in-situ XRD was performed to track the structural evolution (Figure 2A). Under CO treatment, the reflections of Fe 3 O 4 rapidly disappeared at 350 °C and the reflections of Fe 5 C 2 became more intense, suggesting the transition from Fe 3 O 4 to Fe 5 C 2 .…”
Section: The Structural Characterization Of Catalystssupporting
confidence: 57%
“…The results are shown in Supplementary Figures S4 and S5. The MnCuK-FeC catalyst shows signals of Fe 5 C 2 , MnO and CuO in the Raman spectra, while the CuZnAlZr catalyst shows signals of the four metal oxides (CuO, ZnO, Al 2 O 3 , ZrO 2 ), which corresponds to the XPS results in Supplementary Figure S3 (Zhuo et al, 2008;Ahmed et al, 2013;Liu et al, 2014a;Bauer, 2018;Mironova-Ulmane et al, 2018;Lee et al, 2021) Besides, the FT-IR results also show the chemical bonds contained in the two catalysts (Zheng et al, 2013;Jayarambabu, 2014;Elango et al, 2017;Naayi et al, 2018;Chang et al, 2022) The passivated MnCuK-FeC catalyst was pretreated by CO prior to the catalytic reactions, and in-situ XRD was performed to track the structural evolution (Figure 2A). Under CO treatment, the reflections of Fe 3 O 4 rapidly disappeared at 350 °C and the reflections of Fe 5 C 2 became more intense, suggesting the transition from Fe 3 O 4 to Fe 5 C 2 .…”
Section: The Structural Characterization Of Catalystssupporting
confidence: 57%
“…[21][22][23] However, the catalytic performance of Fe-based catalysts without additives is often poor. At present, the commonly used Febased catalyst additives can be divided into electronic additives such as Na, [24][25][26] K, [27][28][29][30] etc., structural additives such as transition metal Mn, [31][32][33] Co, [34][35][36] Cu, [37][38][39] Zn, [40][41][42][43][44] etc. In our group's previous study, [45] it was found that Zn doping was more effective than other transition metal doping in improving the performance of Fe catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of Fischer-Tropsch (FT) synthesis, iron-based catalysts have been used extensively in industrial FT plants [18,19]. The catalytic performance of iron catalysts depends on their active phase, transition metal promoter, alkali promoter, and support [20][21][22][23][24]. It has been shown that FT synthesis over iron catalysts is a structure-sensitive reaction [1,[25][26][27], with the intrinsic reaction rate and product selectivity being functions of iron particle size.…”
Section: Introductionmentioning
confidence: 99%